Clumping of Blood Platelets by Heat Aggregated Gamma-Globulin - Davis, R. B; Holtz, G. C (Thrombosis and Haemostasis, 1969)
The influence of heat-aggregated γ-globulin on the in vitro clumping of rabbit blood platelets was investigated in detail. Clumping was found to be dependent on the amount of γ-globulin added to the system. Clumping began within 60 sec, and was influenced by the amount of heparin in the system. Incubation of platelet-rich plasma with adenosine prior to the addition of heat-aggregated γ-globulin reduced the extent of platelet aggregation but did so only after aggregation was well under way, 150 sec after addition of γ-globulin. The extent of platelet clumping by aggregated γ-globulin was significantly increased by non-aggregating quantities of epinephrine, nor-epinephrine, and 5-hydroxytryptamine in the system; however, bradykinin and histamine were without effect. Electron microscopic observations of platelet aggregates showed that variable destructive changes were present in platelet aggregates, with loss of organelles and platelet hyaloplasm. Marked pseudopod formation was observed in platelet aggregates formed by epinephrine and aggregated γ -globulin. The significance of the findings in relation to the problem of arterial thrombosis is discussed.